i-Diary: A crowdsource-based spatio-Temporal multimedia enhanced points of interest authoring tool - Ahmad, Akhlaq; Ur Rehman, Faizan; ., Md. Abdur Rahman; Murad, Abdullah; ., Ahmad Qamar; Sadiq, Bilal; ., Salah Basalamah; Wahiddin, Mohamed Ridza (The Association for Computing Machinery, 2015)
Aggregating interesting spatio-temporal events of daily life in a diary used to be favorite pastime for many individuals. However, crescive use of social media through portable digital devices is replacing traditional diary writing. Thanks to ubiquity of smartphones, people can now add multiple media types in order to record joyful moments and events with a time line. In this paper, we propose a spatio-temporal multimedia authoring tool by leveraging the ubiquity of geo-tagged multimedia that represents activities of interest to the user and allowing users to aggregate the multimedia for generating a digital diary. The authoring tool allows users to aggregate one’s own spatial media with that of publicly available geo-tagged multimedia artifacts. The complex digital diary can then be saved into a big data repository for personal use as well as for sharing with a community of interest (COI). During the authoring process, the system allows a novel visualization technique of browsing clustered multiple points of interests (CMPOI) at a single GPS location, thereby exploring POIs in a multi-story building, shopping mall, etc. To facilitate efficient and user friendly discovery of CMPOIs, the authoring environment also supports spatio-temporal multimedia queries such as range and KNN (K nearest neighbor) queries from the big data environment. We plan to incorporate this multimedia authoring tool with our existing large scale multimedia supported crowdsourcing environment that is envisioned to support millions of pilgrims during the Hajj 2015 event.